2017
DOI: 10.1007/s10455-017-9559-z
|View full text |Cite
|
Sign up to set email alerts
|

Szegő kernel expansion and equivariant embedding of CR manifolds with circle action

Abstract: We consider a compact connected CR manifold with a transversal CR locally free R-action endowed with a rigid positive CR line bundle. We prove that a certain weighted Fourier-Szegő kernel of the CR sections in the high tensor powers admits a full asymptotic expansion and we establish R-equivariant Kodaira embedding theorem for CR manifolds. Using similar methods we also establish an analytic proof of an R-equivariant Boutet de Monvel embedding theorem for strongly pseudoconvex CR manifolds. In particular, we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 35 publications
(49 reference statements)
0
31
0
Order By: Relevance
“…Suppose now X is irregular and T be the fundamental vector field of the R-action. Take a R-invariant L 2 -inner product on X and consider the weak maximal extension of T on L 2 functions, then in [11] it was shown that T is a self-adjoint operator, and the spectrum of T, denoted by Spec(T), is a countable subset in R. Moreover, all the spectrum of T are eigenvalues. On irregular Sasakian manifolds, it is important to understand the space H 0 b,α (X) := {u ∈ C ∞ (X) : ∂ b u = 0, Tu = iαu}, where ∂ b denotes the tangential Cauchy-Riemann operator on X.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppose now X is irregular and T be the fundamental vector field of the R-action. Take a R-invariant L 2 -inner product on X and consider the weak maximal extension of T on L 2 functions, then in [11] it was shown that T is a self-adjoint operator, and the spectrum of T, denoted by Spec(T), is a countable subset in R. Moreover, all the spectrum of T are eigenvalues. On irregular Sasakian manifolds, it is important to understand the space H 0 b,α (X) := {u ∈ C ∞ (X) : ∂ b u = 0, Tu = iαu}, where ∂ b denotes the tangential Cauchy-Riemann operator on X.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…Proof. The argument is almost the same as the case [5, Section 3] when only circle action is involved, and for the modification to torus action we refer to the proof in [11,Section 4].…”
Section: Proposition 21 the Gaffney Extension And The Weak Maximal mentioning
confidence: 94%
“…Assume that X admits a compact connected Lie group action G. The study of G-equivariant CR functions and Szegő kernel is closely related to some problems in CR, complex geometry, Mathematical physics and geometric quantization theory. For example, for a compact irregular Sasakian manifold X, it was shown in [4] that X admits a torus action T d and the study of torus-equivariant CR functions and Szegő kernel is important in Sasaki geometry. In this work, we consider a compact strongly pseudoconvex CR manifold (X, T 1,0 X) of dimension 2n + 1 and assume that X admits a torus action T d = (e iθ 1 , .…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…Let S k,τ (x, y) ∈ D ′ (X × X) be the distribution kernel of S k,τ . For every λ ∈ R + , it was shown in Lemma 4.6 in [4] that the…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…On the other hand, if a compact three dimensional strongly pseudoconvex CR manifold admits a transversal CR S 1 -action, it was shown by Lempert [Le92], Epstein [Ep92] and recently in [HM14,HHL15] by using the Szegő kernel, that such CR manifolds can always be CR embedded into a complex Euclidean space.…”
Section: Introductionmentioning
confidence: 99%